Coupled eigenfunction expansion–boundary element method for wave scattering by thick vertical barrier over an arbitrary seabed. Issue 1 (2nd January 2021) - Choudhary, A.; Koley, S.; Martha, S. C.
Abstract : Wave structure interaction problem having thick vertical barrier over an arbitrary seabed is analysed for its solution. The associated boundary value problem is handled using a coupled eigenfunction expansion–boundary element method. This method converts the boundary value problem into integral equation over the physical boundaries. The physical boundaries are discretised into a finite number of elements and hence the integral equation give rise to a system of linear algebraic equations. Finally, the system of equations is solved to obtain the physical quantities, namely, the reflection and transmission coefficients. For ensuring the correctness of these physical quantities, the energy balance relation is derived and verified. The present results are also verified by comparing the results available in the literature. The present study reveals that the width and height of the structure along with the undulated seabed play an important role to construct an effective wave barrier to protect various marine facilities from wave attack and also helpful to create the tranquility zone on the lee side of the structure.